IMPLEMENTASI KURIKULUM PENDIDIKAN ISLAM BERKELANJUTAN BERDASARKAN TAFSIR TEMATIK AYAT-AYAT PENDIDIKAN DALAM AL-QUR'AN - Zain, Irfan Ahmad; Saadah, Susi; Aldi, Ujang; Darojat; Rosulina, Desi (UIN Sunan Gunung Djati Bandung, 2025)
Islamic education has a crucial role in building students' character and morals based on Qur'anic values. However, social changes and technological developments require the Islamic education curriculum to continue to adapt. This research aims to analyze the implementation of a sustainable Islamic education curriculum with a thematic interpretation approach to educational verses in the Qur'an. The method used is a literature review, focusing on the curriculum content component in the Qur'an. This curriculum includes the concept of teaching and learning, faith education (aqidah), Islam (shari’a), and ihsan (morals). The concept of teaching and learning is explained in Q.S. Al-'Alaq verses 1-5, which emphasizes the importance of knowledge. Faith education is found in Q.S. Al-Baqarah verse 133, which teaches tawhid. Islamic education is explained in Q.S. An-Nuur verses 56-57, which contains orders for prayer, zakat, and obedience to the Prophet Muhammad SAW. Meanwhile, moral education is found in Q.S. Al-Isra verses 23-24, which emphasizes doing good to parents. This Qur'an-based curriculum is expected to form a relevant and sustainable Islamic education. The results of the research show that the thematic interpretation-based curriculum can integrate intellectual, spiritual, moral, and social aspects in a balanced manner and is relevant to the challenges of the times. The implementation of this curriculum is expected to create Islamic education that not only teaches science but also instills character and moral values that are important in everyday life.